Retaining fruiting trees in the agricultural matrix is important for bird-mediated seed dispersal in a fragmented forest landscape - Jelaine Lim Gan; Katrin M. Meyer; Marion Pfeifer; Terence Craig Soroño; Erwin Somera Torio; Merlijn van Weerd; Marites Gatan-Balbas; Mark David Foster Shirley (Ecological Modelling, 2026)

A review of antimicrobial biodegradable food packaging: design strategies, applications, and challenges - Shan Gao; Loong-Tak Lim; David Julian McClements; Dingkui Qin; Wentao Wang; Hanxue Hou (Food Chemistry, 2026)

Concentrations of 4-hydroxychlorothalonil in serum from pregnant women and the association with risk of testicular germ cell cancer in their male offspring - Cecilie S. Uldbjerg; Christian Lindh; David M. Kristensen; Youn-Hee Lim; Jørgen H. Petersen; Karina M. Sørensen; Panu Rantakokko; Brent A. Coull; Elvira V. Bräuner; Russ Hauser; Niels E. Skakkebæk; Anders Juul; et al. (Environmental Research, 2026)

Analysis of second-generation epigenetic clocks reveals further associations between disproportionate biological ageing and hippocampal volume - Lidija Milicic; Michael Vacher; Vincent Doré; Pierrick Bourgeat; Rosita Shishegar; James D. Doecke; Paul Maruff; Christopher C. Rowe; Victor L. Villemagne; Michael Weiner; Paul Aisen; Ronald Petersen; et al. (GeroScience, 2026)

Utilizing tropical tree rings to trace the spatial and temporal distribution of mercury levels in Cebu, Philippines - Cristi Cesar F. Megraso; Krizella Rhea T. Batulan; Janelle C. Lauron; Jon David C. Suico; A. J. Kenneth P. Sumagang; Jill R. Quitayen; Patrick John Y. Lim (Environmental Science and Pollution Research, 2026)

A 20-kyr record of seawater osmium isotope variations in the Okinawa Trough, a marginal basin in the western Pacific: Implications for climate change - Dhongil Lim; Jihun Kim; Juyeon Yang; Sun Min Choi; Intae Kim; Jeongwon Kang; Zhaokai Xu; David Selby (Palaeogeography, Palaeoclimatology, Palaeoecology, 2026)

The modifying effects of meteorological factors on the association between short-term PM2.5 exposure and daily lung cancer deaths in Jining, China - Yu Jin; Wenhua Duan; David Lim; Mei Wang; Yumin Liang; Zhihui Feng (Atmospheric Pollution Research, 2026)

Interpretable deep learning reveals spatiotemporal MRI features of brain aging that align with neurodegeneration - Nikhil N. Chaudhari; Owen M. Vega; Phoebe Imms; Jaron M. Kawamura; Nahian F. Chowdhury; Tamara Jafar; Andrei Irimia; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2026)
Cortical thinning and atrophy are hallmarks of brain aging that have been characterized using magnetic resonance imaging (MRI). Brain aging involves many neuroanatomic features whose effects on brain structure remain unexplored. To address this challenge, we trained interpretable deep neural networks (DNNs) to estimate brain age (BA) from T 1 -weighted ( T 1 w) MRI. By identifying MRI features unapparent to humans, DNNs can find aging-related structural alterations above and beyond cortical thickness and atrophy. Using a novel approach to DNN interpretability, we mapped brain aging progression in 25,539 cognitively normal UK Biobank adults aged 45–83 years. Cortical aging is found to involve anatomic features becoming prominent during the 50s within frontolateral, mesolimbic, cuneal, and occipitotemporal regions. From these foci, aging-related features propagate to adjacent areas at rates peaking in the 60s. Cortical thinning and atrophy do not trend closely with neurodegeneration, but important DNN-identifiable anatomic features have spatiotemporal dynamics that match those of amyloid or tau. Our results challenge the assumption that MRI cannot map anatomic features trending with neurodegeneration. Interpretable DNNs can empower MRI to quantify anatomic aging as a process of spatial feature expansion from focal regions into nearby structures in the sequence of neurodegenerative pathology. Traditional morphometrics explain only ∼1% of variance in DNN-identifiable features, which clarifies why the former are insensitive to anatomic changes involving neurodegeneration. Our results conceptualize brain aging in the context of spatial and temporal parallels between anatomic senescence and neuropathology. These findings may help to map cognitively normal adults’ neurodegenerative anatomy even without PET measurements. Graphical Abstract

Sex and APOE genotype specific brain regional vulnerability to Alzheimer's Disease - Qi Zeng; Minghui Wang; Erming Wang; Xianxiao Zhou; Peng Xu; Vahram Haroutunian; Dongming Cai; Bin Zhang; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2026)
Alzheimer’s disease (AD) disproportionately affects women and carriers of the apolipoprotein E ε4 allele (APOE4), yet little is known about how sex and APOE interact to influence white matter (WM) integrity during disease progression. We integrated diffusion MRI and matched blood transcriptomic data to investigate these interactions and their underlying biological mechanisms. WM microstructure was quantified using diffusion tensor imaging (DTI) and neurite orientation dispersion and density imaging (NODDI), and regional vulnerability was assessed with a composite vulnerability score (CVS) derived from associations between diffusion features and AD severity across clinical traits in each of the four sex-APOE groups (female or male, with or without APOE4). Brain parcellation with the Eve atlas revealed regions consistently affected across sex-APOE groups (e.g., parahippocampal and superior temporal gyri) and regions specific to individual groups (e.g., the cingulum in females with APOE4 and the middle frontal gyrus in males without APOE4). Gene co-expression network analysis of the matched blood expression data identified gene subnetworks linked to group-specific regional vulnerability, including a muscle tissue morphogenesis module regulated by NEURL1B and HIST1H2BN associated with middle frontal gyrus vulnerability. These findings demonstrate that sex and APOE genotype jointly shape region-specific WM vulnerability and its molecular signatures in AD. Understanding these interactions provides novel mechanistic insights and may inform precision approaches to drug development, biomarker discovery, and clinical trial design for AD.

Optimized crystallization and thermal treatment for high-purity calcium fluoride recovery from fluoride-containing wastewater - Won Kyung Kim; Hyunuk Kang; Ahyeon Lim; Hansol Jang; Yugyeong Kang; Jane Chung; David Inhyuk Kim; Juhyuk Moon (Journal of Cleaner Production, 2026)

A Global Synthesis Suggests Ectomycorrhizal and Arbuscular Mycorrhizal Woody Plants Experience Contrasting Plant–Soil Feedbacks - Xiaoyang Song; Jun Ying Lim; David F. R. P. Burslem (Global Ecology and Biogeography, 2026)
Aim Plant–soil feedbacks (PSFs) are important ecological phenomena that influence plant performance and community assembly. Mycorrhizal fungi, including arbuscular mycorrhizal (AM) and ectomycorrhizal (EcM) fungi, play vital roles in modulating PSFs by mediating plant–soil interactions. However, global patterns of PSFs in relation to mycorrhizal type remain poorly understood. Location Global. Time Period 1994–2022. Major Taxa Studied Woody species. Methods We conducted a meta‐analysis of published data to investigate the difference in the global expression of PSFs between EcM and AM woody plant hosts. Results Our results show that EcM hosts generally experience positive PSFs, whereas AM hosts generally experience negative PSFs, a difference that is consistent across angiosperm and gymnosperm woody plant species. The difference in the mean effect size of PSFs between EcM and AM hosts was strongest for studies conducted in North America and Asia, and was not significant for studies conducted in Europe and Oceania. AM woody species displayed more negative PSFs in wet and cool regions, whereas EcM woody species showed no latitudinal or climatic gradients in the strength of PSFs. These trends resulted in a convergence in the effects of PSFs on EcM and AM woody plants among studies conducted in the tropics, and a significant divergence in temperate and boreal studies. The meta‐analysis also revealed that the expression and detection of PSFs in both AM and EcM woody species are affected by the experimental setting. Main Conclusions Our findings highlight the importance of mycorrhizal type in shaping PSFs and their implications for plant community assembly and dynamics in different biogeographic settings. We discuss how experimental designs influence the detection of PSFs and suggest appropriate methods for future studies.

Advancement in hydrogen production, application and strategy towards sustainable energy: Malaysian case study - Mariam Ameen; Huei Yeong Lim; Haswin Kaur; Nur’aini Raman Yusuf; David Onoja Patrick; Muhammad Shahbaz; Abrar Inayat; Suzana Yusup (Process Safety and Environmental Protection, 2025)

A novel approach for quantifying elongated airborne mineral particles (EMPs) using an automated scanning electron microscope (SEM) - Anushka Elangasinghe; Hamesh Patel; Kim N. Dirks; Ayrton Hamilton; Wenxia (Wendy) Fan; Shuoyu Chen; Nick Talbot; Shanon Lim; Jed Januch; Martin Brook; Brett Wells; David E. Williams; et al. (Atmospheric Environment, 2025)

Uncertainties in ecosystem services assessments and their implications for decision support – A semi-systematic literature review - Franziska Walther; David N. Barton; Jonas Schwaab; Jarumi Kato-Huerta; Bart Immerzeel; Mihai Adamescu; Erling Andersen; Martha Verónica Arámbula Coyote; Ildikó Arany; Mario Balzan; Adriana Bruggeman; Claudia Carvalho-Santos; et al. (Ecosystem Services, 2025)

Long-term effects of emission reduction measures on PM2.5 sources and children’s lung function in Jinan, China - Deai Yang; Pengcheng Zuo; Mingjun Li; David Lim; Liangliang Cui; Zhihui Feng (Environmental Geochemistry and Health, 2025)

Predicting the progression of MCI and Alzheimer’s disease on structural brain integrity and other features with machine learning - Marthe Mieling; Mushfa Yousuf; Nico Bunzeck; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; Susan Landau; Monica Rivera-Mindt; Leslie M. Shaw; Edward B. Lee; et al. (GeroScience, 2025)
Machine learning (ML) on structural MRI data shows high potential for classifying Alzheimer’s disease (AD) progression, but the specific contribution of brain regions, demographics, and proteinopathy remains unclear. Using Alzheimer’s Disease Neuroimaging Initiative (ADNI) data, we applied an extreme gradient-boosting algorithm and SHAP (SHapley Additive exPlanations) values to classify cognitively normal (CN) older adults, those with mild cognitive impairment (MCI) and AD dementia patients. Features included structural MRI, CSF status, demographics, and genetic data. Analyses comprised one cross-sectional multi-class classification (CN vs. MCI vs. AD dementia, n = 568) and two longitudinal binary-class classifications (CN-to-MCI converters vs. CN stable, n = 92; MCI-to-AD converters vs. MCI stable, n = 378). All classifications achieved 70–77% accuracy and 61–83% precision. Key features were CSF status, hippocampal volume, entorhinal thickness, and amygdala volume, with a clear dissociation: hippocampal properties contributed to the conversion to MCI, while the entorhinal cortex characterized the conversion to AD dementia. The findings highlight explainable, trajectory-specific insights into AD progression.

Large language models for diabetes training: a prospective study - Haoxuan Li; Zehua Jiang; Zhouyu Guan; Yuqian Bao; Yuexing Liu; Tingting Hu; Jiajia Li; Ruhan Liu; Liang Wu; Di Cheng; Hongwei Ji; Yong Wang; et al. (Science Bulletin, 2025)

Microbial lysates as low-cost serum replacements in cellular agriculture media formulation - James Dolgin; Damayanti Chakravarty; Sean F. Sullivan; Yiming Cai; Taehwan Lim; Pomaikaimaikalani Yamaguchi; Joseph E. Balkan; Licheng Xu; Aaron D. Olawoyin; Kyongbum Lee; David L. Kaplan; Nikhil U. Nair (Food Research International, 2025)

The need for carbon finance schemes to tackle overexploitation of tropical forest wildlife - Caroline E. Milson; Jun Ying Lim; Daniel J. Ingram; David P. Edwards (Conservation Biology, 2025)
Defaunation of tropical forests, particularly from unsustainable hunting, has diminished populations of key seed dispersers for many tree species, driving shifts in forest community composition toward small‐fruited or wind‐dispersed trees with low wood density. Such shifts can reduce aboveground biomass, prompting calls for overexploitation to be included in bioeconomic policy, but a synthesis of existing literature for wildlife impacts on carbon stores is lacking. We evaluated the role of wildlife in tropical forest tree recruitment and found that it was critical to tropical forest carbon dynamics. The emerging financial value of ecosystem services provided by tropical forest fauna highlights the need for carbon‐based payments for ecosystem services schemes to include wildlife protection. We argue for three cost‐effective actions within carbon finance schemes that can facilitate wildlife protection: support land security opportunities for Indigenous peoples and local communities; provide support for local people to protect forest fauna from overexploitation; and focus on natural regeneration in restoration projects. Incorporating defaunation in carbon‐financing schemes more broadly requires an increased duration of carbon projects and an improved understanding of defaunation impacts on carbon stores and ecosystem‐level models. Without urgent action to halt wildlife losses and prevent empty forest syndrome, the crucial role of tropical forests in tackling climate change may be in jeopardy.

Genomic prediction of survival traits in the response of olive flounder (Paralichthys olivaceus) to viral hemorrhagic septicemia virus: Comparing machine learning models and traditional approaches - D.S. Liyanage; Sukkyoung Lee; Hyerim Yang; Chaehyeon Lim; W.K.M. Omeka; W.M. Gayashani Sandamalika; H.M.V. Udayantha; Gaeun Kim; H.A.C.R. Hanchapola; Subothini Ganeshalingam; Taehyug Jeong; Seong-Rip Oh; et al. (Aquaculture, 2025)

Question-Led Innovation: Public priorities for enhanced weathering research in Malaysia - Emily Cox; Robin Lim; Elspeth Spence; Melissa Payne; David Beerling; Nick Pidgeon (Environmental Science & Policy, 2025)

Assessing nanotoxicity of food-relevant particles: A comparative analysis of cellular responses in cell monolayers versus 3D gut epithelial cultures - Archana Gautam; Hui Kheng Lim; Jasmine Jia’En Li; Christopher Owen Hughes; Calvin Wee Sing Yeo; Moumita Rakshit; David Ian Leavesley; Michelle Jing Sin Lim; Joseph Choon Wee Tan; Li Yi Tan; Joanne Sheot Harn Chan; Benjamin Paul Chapman Smith; et al. (Food and Chemical Toxicology, 2024)

Host response signature trends in persistent bacteraemia and metastatic infection due to Staphylococcus aureus and Gram-negative bacilli: a prospective multicentre observational study - Anna Maria Peri; Nastaran Rafiei; Kevin O’Callaghan; Anna Brischetto; Bianca Graves; Holly Sinclair; Matthew Eustace; Karen Lim; Jill Parkes-Smith; Adam Stewart; Natalie Davidson; Alexis Tabah; et al. (Infectious Diseases, 2024)

Large language models for diabetes care: Potentials and prospects - Bin Sheng; Zhouyu Guan; Lee-Ling Lim; Zehua Jiang; Nestoras Mathioudakis; Jiajia Li; Ruhan Liu; Yuqian Bao; Yong Mong Bee; Ya-Xing Wang; Yingfeng Zheng; Gavin Siew Wei Tan; et al. (Science Bulletin, 2024)

Enhanced volcanic activity and long-term warmth in the middle Eocene revealed by mercury and osmium isotopes from IODP Expedition 369 Site U1514 - Dhongil Lim; Zhaokai Xu; Jihun Kim; Wei Wang; Emma Ownsworth; David Selby; Runsheng Yin; Taesoo Chang (Earth and Planetary Science Letters, 2024)

Land‐use change from market responses to oil palm intensification in Indonesia - Felix K. S. Lim; Luis Roman Carrasco; David P. Edwards; Jolian McHardy (Conservation Biology, 2024)
Oil palm is a major driver of tropical deforestation. A key intervention proposed to reduce the footprint of oil palm is intensifying production to free up spare land for nature, yet the indirect land‐use implications of intensification through market forces are poorly understood. We used a spatially explicit land‐rent modeling framework to characterize the supply and demand of oil palm in Indonesia under multiple yield improvement and demand elasticity scenarios and explored how shifts in market equilibria alter projections of crop expansion. Oil palm supply was sensitive to crop prices and yield improvements. Across all our scenarios, intensification raised agricultural rents and lowered the effectiveness of reductions in crop expansion. Increased yields lowered oil palm prices, but these price‐drops were not sufficient to prevent further cropland expansion from increased agricultural rents under a range of price elasticities of demand. Crucially, we found that agricultural intensification might only result in land being spared when the demand relationship was highly inelastic and crop prices were very low (i.e., a 70% price reduction). Under this scenario, the extent of land spared (∼0.32 million ha) was countered by the continued establishment of new plantations (∼1.04 million ha). Oil palm intensification in Indonesia could exacerbate current pressures on its imperiled biodiversity and should be deployed with stronger spatial planning and enforcement to prevent further cropland expansion.

Globally‐distributed microbial eukaryotes exhibit endemism at deep‐sea hydrothermal vents - Sarah K. Hu; Amy R. Smith; Rika E. Anderson; Sean P. Sylva; Michaela Setzer; Maria Steadmon; Kiana L. Frank; Eric W. Chan; Darlene S. S. Lim; Christopher R. German; John A. Breier; Susan Q. Lang; et al. (Molecular Ecology, 2023)
Single‐celled microbial eukaryotes inhabit deep‐sea hydrothermal vent environments and play critical ecological roles in the vent‐associated microbial food web. 18S rRNA amplicon sequencing of diffuse venting fluids from four geographically‐ and geochemically‐distinct hydrothermal vent fields was applied to investigate community diversity patterns among protistan assemblages. The four vent fields include Axial Seamount at the Juan de Fuca Ridge, Sea Cliff and Apollo at the Gorda Ridge, all in the NE Pacific Ocean, and Piccard and Von Damm at the Mid‐Cayman Rise in the Caribbean Sea. We describe species diversity patterns with respect to hydrothermal vent field and sample type, identify putative vent endemic microbial eukaryotes, and test how vent fluid geochemistry may influence microbial community diversity. At a semi‐global scale, microbial eukaryotic communities at deep‐sea vents were composed of similar proportions of dinoflagellates, ciliates, Rhizaria, and stramenopiles. Individual vent fields supported distinct and highly diverse assemblages of protists that included potentially endemic or novel vent‐associated strains. These findings represent a census of deep‐sea hydrothermal vent protistan communities. Protistan diversity, which is shaped by the hydrothermal vent environment at a local scale, ultimately influences the vent‐associated microbial food web and the broader deep‐sea carbon cycle.

Identification of candidate variants and genes associated with temperature tolerance in olive flounders by Genome-Wide Association Study (GWAS) - H.M.V. Udayantha; Sukkyoung Lee; D.S. Liyanage; Chaehyeon Lim; Taehyug Jeong; W.K.M. Omeka; Hyerim Yang; Gaeun Kim; Joungeun Kim; Jihun Lee; Kishanthini Nadarajapillai; Subothini Ganeshalingam; et al. (Aquaculture, 2023)

Modelling wine grapevines for autonomous robotic cane pruning - Henry Williams; David Smith; Jalil Shahabi; Trevor Gee; Mahla Nejati; Ben McGuinness; Kale Black; Jonathan Tobias; Rahul Jangali; Hin Lim; Mike Duke; Oliver Bachelor; et al. (Biosystems Engineering, 2023)

Potential use of coconut husk-based magnetic sorbent for defoaming application - Felicia Terry Lo; Soh Fong Lim; Sing Ngie David Chua; Kok Keong Lau; Sim Yee Chin (Colloids and Surfaces C: Environmental Aspects, 2023)

Complexation leaching of critical and strategic metals from nickel converter slag using organic acids - Bona Lim; Richard Diaz Alorro; Mark Aylmore; David Grimsey (Minerals Engineering, 2023)

Cyclic behaviour of CLT shear wall hold-down connections using mixed angle self-tapping screws - Thomas Wright; Minghao Li; Daniel Moroder; Hyungsuk Lim; David Carradine (Engineering Structures, 2023)

Low dose γ-radiation induced effects on wax moth (Galleria mellonella) larvae - David Copplestone; Christopher J. Coates; Jenson Lim (Science of The Total Environment, 2023)

Minimal sharing of nosematid and trypanosomatid parasites between honey bees and other bees, but extensive sharing of Crithidia between bumble and mason bees - Haw Chuan Lim; David Lambrecht; Rebecca E. Forkner; T'ai Roulston (Journal of Invertebrate Pathology, 2023)

HDAC inhibitor HPTA initiates anti-tumor response by CXCL9/10-recruited CXCR3+CD4+T cells against PAHs carcinogenicity - Chen Chen; David Lim; Zuchao Cai; Fengmei Zhang; Guochao Liu; Chao Dong; Zhihui Feng (Food and Chemical Toxicology, 2023)

Long-term exposure to air pollution and COVID-19 severity: A cohort study in Greater Manchester, United Kingdom - Samuel Hyman; Jiawei Zhang; Zorana Jovanovic Andersen; Sheena Cruickshank; Peter Møller; Konstantinos Daras; Richard Williams; David Topping; Youn-Hee Lim (Environmental Pollution, 2023)

Predictive liver lipid biomarker signature of Acetyl-coenzyme A carboxylase inhibitor related developmental toxicity in non-pregnant female Han Wistar rats – Lipidomics biomarker discovery and validation - Lauraine Y. Swindale; Alexander J. Stevens; Sarah J. Whalley; Richard A. Currie; K. Michael Jessop; Florence Lai; Pei Pei Lim; Elizabeth F. McInnes; David Cowie; Aniko Kende (Toxicology Letters, 2023)

Technospheric mining of critical and strategic metals from nickel slag – Leaching with citric acid and hydrogen peroxide - Bona Lim; Mark Aylmore; David Grimsey; Richard Diaz Alorro (Hydrometallurgy, 2023)

Long-term exposure to traffic noise and risk of incident colon cancer: A pooled study of eleven Nordic cohorts - Nina Roswall; Jesse D. Thacher; Mikael Ögren; Andrei Pyko; Agneta Åkesson; Anna Oudin; Anne Tjønneland; Annika Rosengren; Aslak H. Poulsen; Charlotta Eriksson; David Segersson; Debora Rizzuto; et al. (Environmental Research, 2023)

Chromosome-length genome assemblies and cytogenomic analyses of pangolins reveal remarkable chromosome counts and plasticity - Marlys L. Houck; Klaus-Peter Koepfli; Taylor Hains; Ruqayya Khan; Suellen J. Charter; Julie A. Fronczek; Ann C. Misuraca; Sergei Kliver; Polina L. Perelman; Violetta Beklemisheva; Alexander Graphodatsky; Shu-Jin Luo; et al. (Chromosome Research, 2023)

Unravelling the synergism of catalytic oxidation and filtration in Co-Mn-oxide impregnated ceramic membrane for intensified degradation of recalcitrant micropollutant with peroxymonosulfate - Arvin Liangdy; Wen Jie Lee; Panyawut Tonanon; Richard David Webster; Shane Allen Snyder; Teik-Thye Lim (Chemical Engineering Journal, 2023)

Determinants of sun bear Helarctos malayanus habitat use in Sabah, Malaysian Borneo and its predicted distribution under future forest degradation and loss - Roshan Guharajan; Jesse F. Abrams; Nicola K. Abram; Hong Ye Lim; Gopalasamy Reuben Clements; Nicolas J. Deere; Matthew J. Struebig; Benoit Goossens; Penny C. Gardner; Jedediah F. Brodie; Alys Granados; Shu Woan Teoh; et al. (Biodiversity and Conservation, 2023)

Integrative epigenomic and transcriptomic analyses reveal metabolic switching by intermittent fasting in brain - Gavin Yong-Quan Ng; Dominic Paul Lee Kok Sheng; Han-Gyu Bae; Sung Wook Kang; David Yang-Wei Fann; Jinsu Park; Joonki Kim; Asfa Alli-Shaik; Jeongmi Lee; Eunae Kim; Sunyoung Park; Jeung-Whan Han; et al. (GeroScience, 2022)

Persistent viral RNA shedding of SARS-CoV-2 is associated with delirium incidence and six-month mortality in hospitalized COVID-19 patients - Ayush Batra; Jeffrey R. Clark; Anthony K. Kang; Sareen Ali; Tulsi R. Patel; Nathan A. Shlobin; Steven C. Hoffman; Patrick H. Lim; Zachary S. Orban; Lavanya Visvabharathy; Edith L. Graham; David P. Sullivan; et al. (GeroScience, 2022)

Comprehensive analysis of epigenetic clocks reveals associations between disproportionate biological ageing and hippocampal volume - Lidija Milicic; Michael Vacher; Tenielle Porter; Vincent Doré; Samantha C. Burnham; Pierrick Bourgeat; Rosita Shishegar; James Doecke; Nicola J. Armstrong; Rick Tankard; Paul Maruff; Colin L. Masters; et al. (GeroScience, 2022)
The concept of age acceleration, the difference between biological age and chronological age, is of growing interest, particularly with respect to age-related disorders, such as Alzheimer’s Disease (AD). Whilst studies have reported associations with AD risk and related phenotypes, there remains a lack of consensus on these associations. Here we aimed to comprehensively investigate the relationship between five recognised measures of age acceleration, based on DNA methylation patterns (DNAm age), and cross-sectional and longitudinal cognition and AD-related neuroimaging phenotypes (volumetric MRI and Amyloid-β PET) in the Australian Imaging, Biomarkers and Lifestyle (AIBL) and the Alzheimer’s Disease Neuroimaging Initiative (ADNI). Significant associations were observed between age acceleration using the Hannum epigenetic clock and cross-sectional hippocampal volume in AIBL and replicated in ADNI. In AIBL, several other findings were observed cross-sectionally, including a significant association between hippocampal volume and the Hannum and Phenoage epigenetic clocks. Further, significant associations were also observed between hippocampal volume and the Zhang and Phenoage epigenetic clocks within Amyloid-β positive individuals. However, these were not validated within the ADNI cohort. No associations between age acceleration and other Alzheimer’s disease-related phenotypes, including measures of cognition or brain Amyloid-β burden, were observed, and there was no association with longitudinal change in any phenotype. This study presents a link between age acceleration, as determined using DNA methylation, and hippocampal volume that was statistically significant across two highly characterised cohorts. The results presented in this study contribute to a growing literature that supports the role of epigenetic modifications in ageing and AD-related phenotypes.

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Examining diversity of terrestrial mammal communities across forest reserves in Sabah, Borneo - Eve Bohnett; Benoit Goossens; Mohd Soffian Abu Bakar; Tommy Rowel Abidin; Hong-Ye Lim; David Hulse; Bilal Ahmad; Thomas Hoctor; Penny Gardner (Biodiversity and Conservation, 2022)

Development of reconstructed intestinal micronucleus cytome (RICyt) assay in 3D human gut model for genotoxicity assessment of orally ingested substances - Hui Kheng Lim; Christopher Owen Hughes; Michelle Jing Sin Lim; Jia’En Jasmine Li; Moumita Rakshit; Calvin Yeo; Kern Rei Chng; Angela Li; Joanne Sheot Harn Chan; Kee Woei Ng; David Ian Leavesley; Benjamin Paul Chapman Smith (Archives of Toxicology, 2022)
The micronucleus (MN) assay is widely used as part of a battery of tests applied to evaluate the genotoxic potential of chemicals, including new food additives and novel food ingredients. Micronucleus assays typically utilise homogenous in vitro cell lines which poorly recapitulate the physiology, biochemistry and genomic events in the gut, the site of first contact for ingested materials. Here we have adapted and validated the MN endpoint assay protocol for use with complex 3D reconstructed intestinal microtissues; we have named this new protocol the reconstructed intestine micronucleus cytome (RICyt) assay. Our data suggest the commercial 3D microtissues replicate the physiological, biochemical and genomic responses of native human small intestine to exogenous compounds. Tissues were shown to maintain log-phase proliferation throughout the period of exposure and expressed low background MN. Analysis using the RICyt assay protocol revealed the presence of diverse cell types and nuclear anomalies (cytome) in addition to MN, indicating evidence for comprehensive DNA damage and mode(s) of cell death reported by the assay. The assay correctly identified and discriminated direct-acting clastogen, aneugen and clastogen requiring exogenous metabolic activation, and a non-genotoxic chemical. We are confident that the genotoxic response in the 3D microtissues more closely resembles the native tissues due to the inherent tissue architecture, surface area, barrier effects and tissue matrix interactions. This proof-of-concept study highlights the RICyt MN cytome assay in 3D reconstructed intestinal microtissues is a promising tool for applications in predictive toxicology.

Cycle Length Evaluation in Persistent Atrial Fibrillation Using Kernel Density Estimation to Identify Transient and Stable Rapid Atrial Activity - Szabolcs Z. Nagy; Patrick Kasi; Valtino X. Afonso; Nathaniel Bird; Brian Pederson; Ian E. Mann; Steven Kim; Nicholas W. F. Linton; David C. Lefroy; Zachary I. Whinnett; Fu Siong Ng; Michael Koa-Wing; et al. (Cardiovascular Engineering and Technology, 2022)
Purpose Left atrial (LA) rapid AF activity has been shown to co-localise with areas of successful atrial fibrillation termination by catheter ablation. We describe a technique that identifies rapid and regular activity. Methods Eight-second AF electrograms were recorded from LA regions during ablation for psAF. Local activation was annotated manually on bipolar signals and where these were of poor quality, we inspected unipolar signals. Dominant cycle length (DCL) was calculated from annotation pairs representing a single activation interval, using a probability density function (PDF) with kernel density estimation. Cumulative annotation duration compared to total segment length defined electrogram quality. DCL results were compared to dominant frequency (DF) and averaging. Results In total 507 8 s AF segments were analysed from 7 patients. Spearman’s correlation coefficient was 0.758 between independent annotators ( P < 0.001), 0.837–0.94 between 8 s and ≥ 4 s segments ( P < 0.001), 0.541 between DCL and DF ( P < 0.001), and 0.79 between DCL and averaging ( P < 0.001). Poorer segment organization gave greater errors between DCL and DF. Conclusion DCL identifies rapid atrial activity that may represent psAF drivers. This study uses DCL as a tool to evaluate the dynamic, patient specific properties of psAF by identifying rapid and regular activity. If automated, this technique could rapidly identify areas for ablation in psAF.

Development of a refined ex vivo model of peritoneal adhesion formation, and a role for connexin 43 in their development - Jia Wang Chua; Leigh Madden; Sophia Beng Hui Lim; Anthony R. J. Philips; David L. Becker (Molecular and Cellular Biochemistry, 2022)

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

Ice‐Ice disease: An environmentally and microbiologically driven syndrome in tropical seaweed aquaculture - Georgia M. Ward; Cicilia S. B. Kambey; Joseph P. Faisan; Pui‐Ling Tan; Caroline C. Daumich; Ivy Matoju; Grant D. Stentiford; David Bass; Phaik‐Eem Lim; Juliet Brodie; Sze‐Wan Poong (Reviews in Aquaculture, 2022)
Seaweeds account for nearly 30% of global aquaculture production by volume, and their cultivation provides important opportunities for employment and wealth generation, particularly in rural coastal communities. Eucheumatoids ( Kappaphycus and Eucheuma spp.) are tropical red algae commercially cultivated as raw material for production of carrageenans, particularly in South‐East Asia and the Western Indian Ocean region. Diseases and pests are major limiting factors in eucheumatoid production, particularly a condition known as ‘ice‐ice’ disease (IID). IID is characterized by bleaching of the thallus followed by the disintegration of affected tissues, leading to a loss of biomass and reduced carrageenan yield. IID has been associated with unfavourable changes in environmental conditions, particularly an increase in sea water temperature and a decrease in salinity, and infection by opportunistic or pathogenic bacteria. However, given that no single or combined causal agents have been definitely identified, IID may be considered a complex pathobiotic syndrome in which multiple factors contribute to the development of disease signs. Here, we review current knowledge of the abiotic and biotic factors associated with the development of IID, and the strategies employed to mitigate economic losses resulting from disease outbreaks. We discuss syndromic diseases in other marine holobionts, particularly other red algae and corals, in relation to their similarity to IID, and suggest the application of comprehensive and complementary methodologies, including high‐throughput sequencing and high‐quality microscopy, for enhancing our understanding of the pathological and microbiological processes associated with IID signs.

Fine-Scale Heterogeneity of a Cold-Water Coral Reef and Its Influence on the Distribution of Associated Taxa - David M. Price; Aaron Lim; Alexander Callaway; Markus P. Eichhorn; Andrew J. Wheeler; Claudio Lo Iacono; Veerle A. I. Huvenne (Frontiers in Marine Science, 2021)
Benthic fauna form spatial patterns which are the result of both biotic and abiotic processes, which can be quantified with a range of landscape ecology descriptors. Fine- to medium-scale spatial patterns (<1–10 m) have seldom been quantified in deep-sea habitats, but can provide fundamental ecological insights into species’ niches and interactions. Cold-water coral reefs formed by Desmophyllum pertusum (syn. Lophelia pertusa ) and Madrepora oculata are traditionally mapped and surveyed with multibeam echosounders and video transects, which limit the ability to achieve the resolution and/or coverage to undertake fine-scale, centimetric quantification of spatial patterns. However, photomosaics constructed from imagery collected with remotely operated vehicles (ROVs) are becoming a prevalent research tool and can reveal novel information at the scale of individual coral colonies. A survey using a downward facing camera mounted on a ROV traversed the Piddington Mound (Belgica Mound Province, NE Atlantic) in a lawnmower pattern in order to create 3D reconstructions of the reef with Structure-from-Motion techniques. Three high resolution orthorectified photomosaics and digital elevation models (DEM) >200 m 2 were created and all organisms were geotagged in order to illustrate their point pattern. The pair correlation function was used to establish whether organisms demonstrated a clustered pattern (CP) at various scales. We further applied a point pattern modelling approach to identify four potential point patterns: complete spatial randomness (CSR), an inhomogeneous pattern influenced by environmental drivers, random clustered point pattern indicating biologically driven clustering and an inhomogeneous clustered point pattern driven by a combination of environmental drivers and biological effects. Reef framework presence and structural complexity determined inhabitant distribution with most organisms showing a departure from CSR. These CPs are likely caused by an affinity to local environmental drivers, growth patterns and restricted dispersion reproductive strategies within the habitat across a range of fine to medium scales. These data provide novel and detailed insights into fine-scale habitat heterogeneity, showing that non-random distributions are apparent and detectable at these fine scales in deep-sea habitats.

NEOTROPICAL ALIEN MAMMALS: a data set of occurrence and abundance of alien mammals in the Neotropics - Clarissa Alves da Rosa; Bruno R. Ribeiro; Vanesa Bejarano; Fernando Henrique Puertas; Adriana Bocchiglieri; Adriana Loeser dos Santos Barbosa; Adriano Garcia Chiarello; Adriano Pereira Paglia; Adriele Aparecida Pereira; Adryelle Francisca de Souza Moreira; Agnis Cristiane de Souza; Aiesca Pellegrin; et al. (Ecology, 2020)
Biological invasion is one of the main threats to native biodiversity. For a species to become invasive, it must be voluntarily or involuntarily introduced by humans into a nonnative habitat. Mammals were among first taxa to be introduced worldwide for game, meat, and labor, yet the number of species introduced in the Neotropics remains unknown. In this data set, we make available occurrence and abundance data on mammal species that (1) transposed a geographical barrier and (2) were voluntarily or involuntarily introduced by humans into the Neotropics. Our data set is composed of 73,738 historical and current georeferenced records on alien mammal species of which around 96% correspond to occurrence data on 77 species belonging to eight orders and 26 families. Data cover 26 continental countries in the Neotropics, ranging from Mexico and its frontier regions (southern Florida and coastal‐central Florida in the southeast United States) to Argentina, Paraguay, Chile, and Uruguay, and the 13 countries of Caribbean islands. Our data set also includes neotropical species (e.g., Callithrix sp., Myocastor coypus , Nasua nasua) considered alien in particular areas of Neotropics. The most numerous species in terms of records are from Bos sp. ( n = 37,782), Sus scrofa ( n = 6,730), and Canis familiaris ( n = 10,084); 17 species were represented by only one record (e.g., S yncerus caffer, Cervus timorensis, Cervus unicolor, Canis latrans ). Primates have the highest number of species in the data set ( n = 20 species), partly because of uncertainties regarding taxonomic identification of the genera Callithrix, which includes the species Callithrix aurita, Callithrix flaviceps, Callithrix geoffroyi, Callithrix jacchus, Callithrix kuhlii, Callithrix penicillata , and their hybrids. This unique data set will be a valuable source of information on invasion risk assessments, biodiversity redistribution and conservation‐related research. There are no copyright restrictions. Please cite this data paper when using the data in publications. We also request that researchers and teachers inform us on how they are using the data.

10th Anniversary of the European Association for Predictive, Preventive and Personalised (3P) Medicine - EPMA World Congress Supplement 2020 - Olga Golubnitschaja; Ondrej Topolcan; Radek Kucera; Vincenzo Costigliola; M. Akopyan; S. N. Akulov; O Alexandrova; Angel Alonso; Russell J. Andrews; A Assuane Duarte; O. Azarova; Maximilian Babel; et al. (EPMA Journal, 2020)
In 2019, the EPMA celebrated its 10th anniversary at the 5th World Congress in Pilsen, Czech Republic. The history of the International Professional Network dedicated to Predictive, Preventive and Personalised Medicine (PPPM / 3PM) is rich in achievements. Facing the coronavirus COVID-19 pandemic it is getting evident globally that the predictive approach, targeted prevention and personalisation of medical services is the optimal paradigm in healthcare demonstrating the high potential to save lives and to benefit the society as a whole. The EPMA World Congress Supplement 2020 highlights advances in 3P medicine.

The Potential Sex Determination Genes, Sox9a and Cyp19a, in Walleye Pollock (Gadus Chalcogrammus) Are Influenced by Water Temperature - So-Sun Kim; David Nahm-Joon Kim; Chang-Ju Lee; Hae-Kyun Yoo; Soon-Gyu Byun; Hyun-Jeong Lim; Jin Choi; Jang-Su Park (Journal of Marine Science and Engineering, 2020)
Our aim was to study the relationship between the sex-determining genes, sox9a and cyp19a, and water temperature in Gadus chalcogrammus. We assessed the sex ratio based on the expression levels of sox9a and cyp19a at different water temperatures (5, 8, 11, and 14 °C) and at different stages of walleye pollock development (embryos, larvae, and juveniles). Next, we used immature walleye pollock to assess sox9a expression in males and cyp19a and vitellogenin (VTG) expression in females at different water temperatures. Males expressed sox9a in the gonadal tissues, while females expressed cyp19a in the gonadal tissues and VTG in the blood plasma. In the first experiment, cyp19a expression was higher at 5 °C and 8 °C, and sox9a expression was higher at 11 and 14 °C. In the second experiment, sox9a expression remained relatively stable, but cyp19a expression decreased with increasing temperature, decreasing significantly after 14 °C. Similar patterns were also observed for VTG expression. These results indicate that lower water temperatures increase cyp19a expression, which increases the female ratio. Higher water temperatures increase sox9a expression, which increases the male ratio. Therefore, this study highlights the potential of the sex-determining genes and the influence of water temperature.

Genetic Ablation of Hematopoietic Cell Kinase Accelerates Alzheimer’s Disease–Like Neuropathology in Tg2576 Mice - Siok Lam Lim; Diana Nguyen Tran; Zanett Kieu; Christine Chen; Emmanuel Villanueva; Sagar Ghiaar; Victoria Gallup; Joannee Zumkehr; David H. Cribbs; Carlos J. Rodriguez-Ortiz; Masashi Kitazawa (Molecular Neurobiology, 2020)

TRY plant trait database – enhanced coverage and open access - Jens Kattge; Gerhard Bönisch; Sandra Díaz; Sandra Lavorel; Iain Colin Prentice; Paul Leadley; Susanne Tautenhahn; Gijsbert D. A. Werner; Tuomas Aakala; Mehdi Abedi; Alicia T. R. Acosta; George C. Adamidis; et al. (Global Change Biology, 2020)
Plant traits—the morphological, anatomical, physiological, biochemical and phenological characteristics of plants—determine how plants respond to environmental factors, affect other trophic levels, and influence ecosystem properties and their benefits and detriments to people. Plant trait data thus represent the basis for a vast area of research spanning from evolutionary biology, community and functional ecology, to biodiversity conservation, ecosystem and landscape management, restoration, biogeography and earth system modelling. Since its foundation in 2007, the TRY database of plant traits has grown continuously. It now provides unprecedented data coverage under an open access data policy and is the main plant trait database used by the research community worldwide. Increasingly, the TRY database also supports new frontiers of trait‐based plant research, including the identification of data gaps and the subsequent mobilization or measurement of new data. To support this development, in this article we evaluate the extent of the trait data compiled in TRY and analyse emerging patterns of data coverage and representativeness. Best species coverage is achieved for categorical traits—almost complete coverage for ‘plant growth form’. However, most traits relevant for ecology and vegetation modelling are characterized by continuous intraspecific variation and trait–environmental relationships. These traits have to be measured on individual plants in their respective environment. Despite unprecedented data coverage, we observe a humbling lack of completeness and representativeness of these continuous traits in many aspects. We, therefore, conclude that reducing data gaps and biases in the TRY database remains a key challenge and requires a coordinated approach to data mobilization and trait measurements. This can only be achieved in collaboration with other initiatives.

Biomechanical analysis of proximal tibia bone grafting and the effect of the size of osteotomy using a validated finite element model - David Q. K. Ng; Chin Tat Lim; Amit K. Ramruttun; Ken Jin Tan; Wilson Wang; Desmond Y. R. Chong (Medical & Biological Engineering & Computing, 2019)

Staphylococcal driveline infections are the predominant type of left ventricular assist device associated infections in Singapore - Yii Ean Teh; Choon Pin Lim; Louis Loon Yee Teo; Jia Lin Soon; Victor Tar Toong Chao; Chia Lee Neo; Joycelyn Li Li Tan; Ka Lee Kerk; David Kheng Leng Sim; Teing Ee Tan; Ban Hock Tan; Sivathasan Cumaraswamy; et al. (Infectious Diseases, 2019)

Kynurenine 3-Monooxygenase Activity in Human Primary Neurons and Effect on Cellular Bioenergetics Identifies New Neurotoxic Mechanisms - Gloria Castellano-Gonzalez; Kelly R. Jacobs; Emily Don; Nicholas J. Cole; Seray Adams; Chai K. Lim; David B. Lovejoy; Gilles J. Guillemin (Neurotoxicity Research, 2019)

Origin of complex zoning in olivine from diverse, diamondiferous kimberlites and tectonic settings: Ekati (Canada), Alto Paranaiba (Brazil) and Kaalvallei (South Africa) - Emilie Lim; Andrea Giuliani; David Phillips; Karsten Goemann (Mineralogy and Petrology, 2018)

Correction to: Physiological resolution of periodic breath holding during heavy-intensity Fartlek exercise - David J. Lim; Jae J. Kim; Greg D. Marsh; Glen R. Belfry (European Journal of Applied Physiology, 2018)

Physiological resolution of periodic breath holding during heavy-intensity Fartlek exercise - David J. Lim; Jae J. Kim; Greg D. Marsh; Glen R. Belfry (European Journal of Applied Physiology, 2018)

Effects of fatty acid amide hydrolase inhibitor URB597 in a rat model of trauma-induced long-term anxiety - Andalib Danandeh; Valentina Vozella; James Lim; Fariba Oveisi; Gina L. Ramirez; David Mears; Gary Wynn; Daniele Piomelli (Psychopharmacology, 2018)

Probability discounting of treatment decisions in multiple sclerosis: associations with disease knowledge, neuropsychiatric status, and adherence - Jared M. Bruce; Amanda S. Bruce; Sharon Lynch; Joanie Thelen; Seung-Lark Lim; Julia Smith; Delwyn Catley; Derek D. Reed; David P. Jarmolowicz (Psychopharmacology, 2018)

Abundance and Distribution of the Potentially Toxic Thecate Dinoflagellate Alexandrium tamiyavanichii (Dinophyceae) in the Central Mexican Pacific, Using the Quantitative PCR Method - David U. Hernández-Becerril; Winnie L. S. Lau; Kieng S. Hii; Chui P. Leaw; F. Varona-Cordero; Po T. Lim (Frontiers in Marine Science, 2018)

Refining Protein Penetration into the Lipid Bilayer Using Fluorescence Quenching and Molecular Dynamics Simulations: The Case of Diphtheria Toxin Translocation Domain - Alexander Kyrychenko; Nathan M. Lim; Victor Vasquez-Montes; Mykola V. Rodnin; J. Alfredo Freites; Linh P. Nguyen; Douglas J. Tobias; David L. Mobley; Alexey S. Ladokhin (The Journal of Membrane Biology, 2018)

Converging and emerging threats to health security - C. Raina MacIntyre; Thomas Edward Engells; Matthew Scotch; David James Heslop; Abba B. Gumel; George Poste; Xin Chen; Wesley Herche; Kathleen Steinhöfel; Samsung Lim; Alex Broom (Environment Systems and Decisions, 2018)

Evidence that NF-κB and MAPK Signaling Promotes NLRP Inflammasome Activation in Neurons Following Ischemic Stroke - David Yang-Wei Fann; Yun-An Lim; Yi-Lin Cheng; Ker-Zhing Lok; Prasad Chunduri; Sang-Ha Baik; Grant R. Drummond; S. Thameem Dheen; Christopher G. Sobey; Dong-Gyu Jo; Christopher Li-Hsian Chen; Thiruma V. Arumugam (Molecular Neurobiology, 2018)

Political transition and emergent forest‐conservation issues in Myanmar - Graham W. Prescott; William J. Sutherland; Daniel Aguirre; Matthew Baird; Vicky Bowman; Jake Brunner; Grant M. Connette; Martin Cosier; David Dapice; Jose Don T. De Alban; Alex Diment; Julia Fogerite; et al. (Conservation Biology, 2017)
Political and economic transitions have had substantial impacts on forest conservation. Where transitions are underway or anticipated, historical precedent and methods for systematically assessing future trends should be used to anticipate likely threats to forest conservation and design appropriate and prescient policy measures to counteract them. Myanmar is transitioning from an authoritarian, centralized state with a highly regulated economy to a more decentralized and economically liberal democracy and is working to end a long‐running civil war. With these transitions in mind, we used a horizon‐scanning approach to assess the 40 emerging issues most affecting Myanmar's forests, including internal conflict, land‐tenure insecurity, large‐scale agricultural development, demise of state timber enterprises, shortfalls in government revenue and capacity, and opening of new deforestation frontiers with new roads, mines, and hydroelectric dams. Averting these threats will require, for example, overhauling governance models, building capacity, improving infrastructure‐ and energy‐project planning, and reforming land‐tenure and environmental‐protection laws. Although challenges to conservation in Myanmar are daunting, the political transition offers an opportunity for conservationists and researchers to help shape a future that enhances Myanmar's social, economic, and environmental potential while learning and applying lessons from other countries. Our approach and results are relevant to other countries undergoing similar transitions.

Left ventricular flow propagation velocity measurement: Is it cast in stone? - Bee Ting Chan; Hak Koon Yeoh; Yih Miin Liew; Yang Faridah Abdul Aziz; Ganiga Srinivasaiah Sridhar; Christian Hamilton-Craig; David Platts; Einly Lim (Medical & Biological Engineering & Computing, 2017)

Denial of long‐term issues with agriculture on tropical peatlands will have devastating consequences - Lahiru S. Wijedasa; Jyrki Jauhiainen; Mari Könönen; Maija Lampela; Harri Vasander; Marie‐Claire Leblanc; Stephanie Evers; Thomas E. L. Smith; Catherine M. Yule; Helena Varkkey; Massimo Lupascu; Faizal Parish; et al. (Global Change Biology, 2017)

Performance on the Cogstate Brief Battery Is Related to Amyloid Levels and Hippocampal Volume in Very Mild Dementia - Yen Ying Lim; Victor L. Villemagne; Simon M. Laws; Robert H. Pietrzak; David Ames; Christopher Fowler; Stephanie Rainey-Smith; Peter J. Snyder; Pierrick Bourgeat; Ralph N. Martins; Olivier Salvado; Christopher C. Rowe; et al. (Journal of Molecular Neuroscience, 2016)

Isolation of High-Lipid Tetraselmis suecica Strains Following Repeated UV-C Mutagenesis, FACS, and High-Throughput Growth Selection - David K. Y. Lim; Holger Schuhmann; Kalpesh Sharma; Peer M. Schenk (BioEnergy Research, 2015)

Extraction optimisation and isolation of triterpenoids from Ganoderma lucidum and their effect on human carcinoma cell growth - Weimei Ruan; Andrew Hiang He Lim; Lau Gek Huang; David G. Popovich (Natural Product Research, 2014)

Beta-2 adrenergic receptors mediate stress-evoked reinstatement of cocaine-induced conditioned place preference and increases in CRF mRNA in the bed nucleus of the stria terminalis in mice - Jayme R. McReynolds; Oliver Vranjkovic; Malia Thao; David A. Baker; Khadijah Makky; Yiwei Lim; John R. Mantsch (Psychopharmacology, 2014)

Causes and predictability of the record wet east Australian spring 2010 - Harry H. Hendon; Eun-Pa Lim; Julie M. Arblaster; David L. T. Anderson (Climate Dynamics, 2014)

Effects of probiotics supplementation on gastrointestinal permeability, inflammation and exercise performance in the heat - Cecilia M. Shing; Jonathan M. Peake; Chin Leong Lim; David Briskey; Neil P. Walsh; Matthew B. Fortes; Kiran D. K. Ahuja; Luis Vitetta (European Journal of Applied Physiology, 2014)

Isotopic labeling of the heme cofactor in cytochrome p450 and other heme proteins - David Bryson; Pek-Lang Lim; Alin Lawson; Sandhya Manjunath; Gregory M. Raner (Biotechnology Letters, 2011)

Species of Neohaliotrema Yamaguti, 1965 (Monogenea: Ancyrocephalidae) from the pomacentrid Abudefduf vaigensis (Quoy & Gaimard) off Pulau Langkawi, Malaysia, with a revised diagnosis of the genus and a key to its species - L. H. S. Lim; David I. Gibson (Systematic Parasitology, 2010)

Deforestation and Avian Extinction on Tropical Landbridge Islands - NAVJOT S. SODHI; DAVID S. WILCOVE; TIEN MING LEE; CAGAN H. SEKERCIOGLU; R. SUBARAJ; HENRY BERNARD; DING LI YONG; SUSAN L. H. LIM; DEWI M. PRAWIRADILAGA; BARRY W. BROOK (Conservation Biology, 2010)
There are few empirical data, particularly collected simultaneously from multiple sites, on extinctions resulting from human‐driven land‐use change. Southeast Asia has the highest deforestation rate in the world, but the resulting losses of biological diversity remain poorly documented. Between November 2006 and March 2008, we conducted bird surveys on six landbridge islands in Malaysia and Indonesia. These islands were surveyed previously for birds in the early 1900s, when they were extensively forested. Our bird inventories of the islands were nearly complete, as indicated by sampling saturation curves and nonparametric true richness estimators. From zero (Pulau Malawali and Pulau Mantanani) to 15 (Pulau Bintan) diurnal resident landbird species were apparently extirpated since the early 1900s. Adding comparable but published extinction data from Singapore to our regression analyses, we found there were proportionally fewer forest bird extinctions in areas with greater remaining forest cover. Nevertheless, the statistical evidence to support this relationship was weak, owing to our unavoidably small sample size. Bird species that are restricted to the Indomalayan region, lay few eggs, are heavier, and occupy a narrower habitat breadth, were most vulnerable to extinction on Pulau Bintan. This was the only island where sufficient data existed to analyze the correlates of extinction. Forest preservation and restoration are needed on these islands to conserve the remaining forest avifauna. Our study of landbridge islands indicates that deforestation may increasingly threaten Southeast Asian biodiversity.

Description of Sinodiplectanotrema malayanum n. sp. (Monogenea: Diplectanidae), with comments on the taxonomic position of the genus - L. H. S. Lim; W. B. Tan; David I. Gibson (Systematic Parasitology, 2010)

Costimulation of Th17 cells: adding fuel or putting out the fire in the inflamed gut? - Zili Zhang; James T. Rosenbaum; Wenwei Zhong; Carmen Lim; David J. Hinrichs (Seminars in Immunopathology, 2010)

Insect extinctions on a small denuded Bornean island - Navjot S. Sodhi; David S. Wilcove; R. Subaraj; Ding Li Yong; Tien Ming Lee; Henry Bernard; Susan L. H. Lim (Biodiversity and Conservation, 2010)

Phylogeography of the magpie‐robin species complex (Aves: Turdidae: Copsychus ) reveals a Philippine species, an interesting isolating barrier and unusual dispersal patterns in the Indian Ocean and Southeast Asia - Frederick H. Sheldon; David J. Lohman; Haw C. Lim; Fasheng Zou; Steven M. Goodman; Dewi M. Prawiradilaga; Kevin Winker; Thomas M. Braile; Robert G. Moyle (Journal of Biogeography, 2009)
Aim The oriental magpie‐robin ( Copsychus saularis ) of South and Southeast Asia is a phenotypically variable species that appears to be closely related to two endemic species of the western Indian Ocean: the Madagascar magpie‐robin ( Copsychus albospecularis ) and the Seychelles magpie‐robin ( Copsychus sechellarum ). This unusual distribution led us to examine evolutionary relationships in magpie‐robins, and also the taxonomic significance of their plumage variation, via a molecular phylogenetic and population genetic analysis of C. saularis and C. albospecularis . Location Southern Asia from Nepal across Indochina to southern China, and the Indian Ocean from Madagascar to the Greater Sunda and Philippine islands. Methods We sequenced 1695 nucleotides of mitochondrial DNA comprising the complete second subunit of the nicotinamide adenine dinucleotide dehydrogenase (ND2) gene and 654 bases of the cytochrome c oxidase subunit I (COI) region in 51 individuals of eight C. saularis subspecies, 10 individuals of C. albospecularis (one subspecies) and single individuals of two other Copsychus species as outgroups. The data were analysed phylogenetically, with maximum likelihood, Bayesian, relaxed clock and parsimony methods, and geographically for patterns of genetic diversity. Results Phylogenetic analysis indicated that C. albospecularis lies within the nominal C. saularis , making C. saularis polyphyletic. Malagasy and non‐Philippine Asian populations form a monophyletic group that is sister to a clade of Philippine populations. Within non‐Philippine Asian populations, two groups are evident: black‐bellied birds in the eastern Greater Sunda islands and white‐bellied birds in the western Sundas and on mainland Asia. Main conclusions The phylogeny of magpie‐robins suggests a novel pattern of dispersal and differentiation in the Old World. Ancestral magpie‐robins appear to have spread widely among islands of the Indian Ocean in the Pliocene, probably aided by their affinity for coastal habitats. Populations subsequently became isolated in island groups, notably the Philippines, Madagascar and the Greater Sundas, leading to speciation in all three areas. Isolation in the Philippines may have been aided by competitive exclusion of C. saularis from Palawan by a congener, the white‐vented shama ( Copsychus niger ). In the Greater Sundas, white‐bellied populations appear to have invaded Borneo and Java recently, where they hybridize with resident black‐bellied birds.

A new monogenean genus from an ephippid fish off Peninsular Malaysia - L. H. S. Lim; David I. Gibson (Systematic Parasitology, 2009)

Species of Triacanthinella Bychowsky & Nagibina, 1968 (Monogenea: Ancyrocephalidae) from triacanthid teleosts off Peninsular Malaysia, with a generic revision, amended diagnosis and key - L. H. S. Lim; David I. Gibson (Systematic Parasitology, 2008)

Redescriptions of species of Ancyrocephaloides Yamaguti, 1938 (Monogenea: Ancyrocephalidae) from triacanthid fishes caught off Peninsular Malaysia and a report of their haptoral secretions - L. H. S. Lim; David I. Gibson (Systematic Parasitology, 2007)

Hydrostratigraphy and geochemistry at a coastal sandfill in Singapore - Lloyd H. C. Chua; Edmond Y. M. Lo; David L. Freyberg; E. B. Shuy; T. T. Lim; S. K. Tan; Mzila Ngonidzashe (Hydrogeology Journal, 2007)

The reference genetic linkage map for the multinational Brassica rapa genome sequencing project - Su Ryun Choi; Graham R. Teakle; Prikshit Plaha; Jeong Hee Kim; Charlotte J. Allender; Elena Beynon; Zhong Yun Piao; Pilar Soengas; Tae Ho Han; Graham J. King; Guy C. Barker; Paul Hand; et al. (Theoretical and Applied Genetics, 2007)

Poster abstracts - J. Ferrie; M. Shipley; F. Cappuccio; E. Brunner; M. Miller; M. Kumari; M. Marmot; A. Coenen; J. L. Castillo; F. Araya; G. Bustamante; L. Montecino; et al. (Sleep and Biological Rhythms, 2007)

Coxsackievirus B3 proteases 2A and 3C induce apoptotic cell death through mitochondrial injury and cleavage of eIF4GI but not DAP5/p97/NAT1 - David H. W. Chau; Ji Yuan; Huifang Zhang; Paul Cheung; Travis Lim; Zhen Liu; Alhousseynou Sall; Decheng Yang (Apoptosis, 2007)

Impact of Firm‐Based Environmental Standards on Subsidiaries and Their Suppliers: Evidence from Motorola‐Penang - Michael T. Rock; Pao Li Lim; David P. Angel (Journal of Industrial Ecology, 2006)
How successful are multinational corporations in extending their firm‐based environmental standards to their subsidiaries and those subsidiaries' local suppliers in their global production networks in developing countries? We address this question through an in‐depth case study of how Motorola, a prominent multinational electronics firm with an extensive global production network, is using a set of firm‐based standards to meet several new stringent European Union environmental directives. The case study demonstrates that these firm‐based standards appear to be enabling a major subsidiary and its suppliers in one developing economy to reduce the environmental intensities of their production activities. This finding suggests that the firm‐based environmental standards of multinationals with extensive global production networks might contribute to a leveling up of environmental standards in subsidiaries and their local suppliers, rather than a “race to the bottom”, thus reinforcing the technique or intensity effects associated with open trade, investment, and technology policies.

Normal but not altered mucins activate neutrophils - Marie-Laure Rachel Aknin; Monica Berry; Andrew David Dick; Doreen Khan-Lim (Cell and Tissue Research, 2004)

Genomic and Phylogenetic Analysis of the S100A7 (Psoriasin) Gene Duplications Within the Region of the S100 Gene Cluster on Human Chromosome 1q21 - Jerzy K. Kulski; Chew Ping K. Lim; David S. Dunn; Matthew Bellgard (Journal of Molecular Evolution, 2003)

Picoplankton and nanoplankton and their trophic coupling in surface waters of the Sargasso Sea south of Bermuda - David A. Caron; Emily R. Peele; Ee Lin Lim; Mark R. Dennett (Limnology and Oceanography, 1999)
Studies were conducted during August and March–April in the Sargasso Sea south of Bermuda to examine rates of bacterial growth and picoplankton consumption by microbial consumers. Bacterial growth rates were estimated from [ 3 H]thymidine (TdR) incorporation rates, while grazing rates were determined using fluorescently labeled prey (FLP). In addition, net bacterial growth rates were calculated from changes in bacterial abundance during 24‐h incubations. The latter measurements were compared to net growth rates obtained by subtracting picoplankton grazing mortality rates from bacterial TdR growth rate estimates (TdR minus FLP). Overall, bacterial growth rates determined by TdR uptake were similar to FLP grazing rates during the March–April cruise, indicating an approximate balance between production and removal processes. Bacterial growth rates during August, however, were approximately twice the rates of grazer removal. Net bacterial growth rates determined from TdR growth rates minus FLP grazing rates were similar to net growth rates estimated from changes in abundance for samples collected near the surface during both cruises. However, rates of change of bacterial abundances during incubations were generally greater than rates predicted from TdR minus FLP for samples collected in the deep euphotic zone during both cruises. These discrepancies might be explained by several factors, including the inclusion of prochlorophytes in the bacterial counts and/or the stimulation of bacterial growth during containment. The TdR conversion factor also was an important consideration when comparing net bacterial growth rates estimated from changes in bacterial abundance to net growth rates determined from TdR minus FLP. Small nanoplanktonic protists (

The ecology of Paraphysomonas imperforata based on studies employing oligonucleotide probe identification in coastal water samples and enrichment cultures - Ee Lin Lim; Mark R. Dennett; David A. Caron (Limnology and Oceanography, 1999)
The geographical distribution and seasonal abundance of the cosmopolitan heterotrophic flagellate Paraphysomonas imperforata in several coastal waters was examined using species‐specific oligonucleotide hybridization probes which target small subunit ribosomal RNA. P. imperforata was found to occur in several coastal environments, but at very low abundances (typically −1 ). The seasonal abundance of P. imperforata examined at one sampling site remained consistently low and constituted no more than 1% of the total nanoplankton at any time during a 17‐month sampling period. In contrast to the low abundances observed in natural water samples, P. imperforata frequently dominated heterotrophic enrichment cultures prepared from these same samples, comprising up to 98% of the total nanoplankton. Based on these findings, we conclude that P. imperforata is an opportunistic species capable of growing rapidly to high abundances when prey concentrations are high. Water and enrichment temperature as well as the temperature tolerance range of P. imperforata appear to have played a role in the seasonal differences observed in P. imperforata dominance. Experiments with enrichment cultures indicated that the absolute abundances of P. imperforata in the water samples and the activity of consumers of nanoplankton also influenced the degree to which P. imperforata dominated the heterotrophic nanoplankton assemblages of enrichment cultures. Seasonal changes in water temperature might also affect these latter factors, and, as a consequence, indirectly influence the ability of P. imperforata populations to dominate enrichments. Our results support the notion that enrichment cultivation of heterotrophic flagellates, and perhaps incubations in general, can select for species such as P. imperforata that may not be representative of nanoplanktonic protists that numerically dominate natural assemblages.